Remote beam output audits: A global assessment of results out of tolerance. (July 2018) - Kry, Stephen F.; Peterson, Christine B.; Howell, Rebecca M.; Izewska, Joanna; Lye, Jessica; Clark, Catharine H.; Nakamura, Mitsuhiro; Hurkmans, Coen; Alvarez, Paola; Alves, Andrew; Bokulic, Tomislav; Followill, David; et al.
Abstract: Background and purpose: Remote beam output audits, which independently measure an institution's machine calibration, are a common component of independent radiotherapy peer review. This work reviews the results and trends of these audit results across several organisations and geographical regions. Materials and methods: Beam output audit results from the Australian Clinical Dosimetry Services, International Atomic Energy Agency, Imaging and Radiation Oncology Core, and Radiation Dosimetry Services were evaluated from 2010 to the present. The rate of audit results outside a ±5% tolerance was evaluated for photon and electron beams as a function of the year of irradiation and nominal beam energy. Additionally, examples of confirmed calibration errors were examined to provide guidance to clinical physicists and auditing bodies. Results: Of the 210, 167 audit results, 1323 (0.63%) were outside of tolerance. There was a clear trend of improved audit performance for more recent dates, and while all photon energies generally showed uniform rates of results out of tolerance, low (6 MeV) and high (≥18 MeV) energy electron beams showed significantly elevated rates. Twenty nine confirmed calibration errors were explored and attributed to a range of issues, such as equipment failures, errors in setup, and errors in performing the clinical reference calibration. Forty-two percent of these confirmed errors were detected during ongoing periodic monitoring, and not at the time of the first audit of the machine. Conclusions: Remote beam output audits have identified, and continue to identify, numerous and often substantial beam calibration errors.